2022
DOI: 10.1021/acs.inorgchem.2c02263
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Trapen Ligand-Based U(IV) and Th(IV) 2-Phosphaethynolate Complexes and Comparison of Covalency with Corresponding Ti(IV) Analogues

Abstract: The involvement of the 2-phosphaethynolate anion species with ambident nucleophilic properties serves as an essential protocol for synthesizing oxygen-bound or phosphorus-bound complexes. This work mainly describes the synthesis and characterization of U, Th, and Ti phosphaethynolate complexes featuring a preferential O-coordination fashion. Among these complexes, the first examples of a Ti(IV)-OCP complex 3A, Th(IV)-OCP complex 3B, and U(IV)-OCP complex 3C were assembled by a salt metathesis reaction between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…Complex 1 , [(Trapen TMS )­Ce­(THF)] (Trapen = tris (2-aminobenzyl)­amine; TMS = SiMe 3 ), was prepared with satisfactory yield by the reaction of [(Trapen TMS )­(Li) 3 ] with CeCl 3 (THF) 2 in THF at −30 °C, following an analogous route previously reported for (TriNO x )­Ce­(THF) (Scheme ). The molecular structure of complex 1 was characterized by single-crystal X-ray diffraction and multinuclear NMR spectroscopy.…”
Section: Resultsmentioning
confidence: 99%
“…Complex 1 , [(Trapen TMS )­Ce­(THF)] (Trapen = tris (2-aminobenzyl)­amine; TMS = SiMe 3 ), was prepared with satisfactory yield by the reaction of [(Trapen TMS )­(Li) 3 ] with CeCl 3 (THF) 2 in THF at −30 °C, following an analogous route previously reported for (TriNO x )­Ce­(THF) (Scheme ). The molecular structure of complex 1 was characterized by single-crystal X-ray diffraction and multinuclear NMR spectroscopy.…”
Section: Resultsmentioning
confidence: 99%
“…Currently, there are several screening methods for ion-imprinted polymer functional monomers: [29][30][31] (1) ultraviolet spectroscopy, which is the most commonly used method for screening ion-imprinted functional monomers; (2) ion simulation technology, where computer simulation soware is used to simulate the interaction forces between template ions and some functional monomers and to calculate the magnitude of these forces, enabling the best functional monomers to be selected; (3) nuclear magnetic resonance spectroscopy (NMR), which can also be used to screen functional monomers. [32][33][34][35][36] However, these methods have some limitations. For example, ultraviolet spectroscopy is mainly suitable for the screening of functional monomers containing special functional groups; some substances without absorption peaks in the ultraviolet range cannot be screened by this method.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, some related studies have shown that tripod ligands have advantages in the construction of fivecoordinate triangular bipyramidal complexes. [27][28][29][30][31][32] Inspired by previous work, we were interested in preparing a new class of five-coordinate triangular bipyramid mononuclear Dy III -based SIMs with local D 3h symmetry. For deeper understanding of magneto-structural correlation and detailed theoretical elucidations of the dynamic magnetic behaviors in five-coordinate Dy III SIMs.…”
Section: Introductionmentioning
confidence: 99%